Lease of Noxious Gases During Burning of Mosquito Coils: A Pilot Study - Beah, Joe Milton; Taylor, Eldred Tunde; Kamara, Thomas Fayia; Kaitibi, Daniel (International Journal of Sustainable Energy and Environmental Research, 2016)
Indoor air pollution due to combusting biomass fuels is a serious problem in developing countries and the impact to a greater extent is less known from burning mosquito coils. As malaria is a major killer in developing countries, the use of mosquito repellants would continue to be used in millions of homes across the continent of Africa. Hence this pilot study was conducted to assess emission levels of nitrogen dioxide (NO2); sulphur dioxide (SO2) and carbon monoxide (CO) during the burning of six different products of mosquito coils that are sold in Sierra Leone. One hour emission value was recorded for each product during the burning period. Result revealed that one hour SO2 concentrations range from not detected to 47 ppb and that for CO range from 16 ppm to 19 ppm for the different products. Evidence of high peak values was observed for both SO2 and CO for the different products which is clearly a public health concern. This pilot study demonstrated that burning mosquito coils in less ventilated rooms where the primary focus is to eliminate mosquitoes is an environmental health risk in Sierra Leone.